2018
DOI: 10.1111/josh.12682
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Weight Discrimination and School Connectedness Among Youth: Does Teacher Support Play a Protective Role?

Abstract: The association between weight discrimination and low levels of school connectedness is important as students spend most of their time at school and should benefit from the positive effects of feeling connected to school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 71 publications
(125 reference statements)
1
7
0
1
Order By: Relevance
“…Our findings on belonging with classmates and with teachers were in line with previous research suggesting negative relations with physiological stress, depressive symptoms, and positive relations with school engagement (Kiang et al, 2011;Golaszewski et al, 2018;Slaten et al, 2016). The results confirm that both classmate and teacher support is relevant to fostering school engagement and better health among adolescents of immigrant descent (Göbel & Preusche, 2019).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Our findings on belonging with classmates and with teachers were in line with previous research suggesting negative relations with physiological stress, depressive symptoms, and positive relations with school engagement (Kiang et al, 2011;Golaszewski et al, 2018;Slaten et al, 2016). The results confirm that both classmate and teacher support is relevant to fostering school engagement and better health among adolescents of immigrant descent (Göbel & Preusche, 2019).…”
supporting
confidence: 91%
“…In school contexts, belonging is pivotal for successful academic and socioemotional adjustment (Golaszewski et al, 2018;Slaten et al, 2016). School belonging refers to a student's perception and experience of safety, connectedness, and teacher fairness and support at school (Libbey, 2004).…”
Section: Belonging With Classmates and With Teachersmentioning
confidence: 99%
“…The lower level of PWS during COVID-19 outbreak and postlockdown may be explained by the diminished social interaction, and hence, fewer chances to be stigmatized. Mainly, children experienced weight-based teasing and bullying at school (42)(43)(44). Research showed that children who experienced weightbased teasing were likely to perform avoidance behaviors such as skipping school, suggesting that escaping social interaction could be a relief (44).…”
Section: Discussionmentioning
confidence: 99%
“…Lo que genera costos sociales altos tanto en hombres como en mujeres debido a la discriminación ocasionada por estereotipos y prejuicios (Pearl et al 2018). Las personas con exceso de peso tienen desventaja en instituciones educativas (Golaszewski et al 2018), en los servicios de salud (Barra y Singh, 2018) y en actividades de recreación tales como hoteles y restaurantes (Poria, et al 2021); asimismo, perciben salarios más bajos y presentan ausentismo laboral según la Organización para la Cooperación y Desarrollo Económico (Agencia Reforma, 20 de mayo de 2017). Comúnmente, estos estereotipos de belleza suelen ser "imágenes distorsionadas y cargadas de prejuicios acerca de toda una categoría de personas" (Macionis, 2011, p. 302), incluidas las que padecen exceso de peso.…”
Section: Estigma Y Re-significación Social De Los Agentesunclassified